Using Texting for Clinical Communication in Surgery: A Survey of Academic Staff Surgeons. (June 2018) - Firdouse, Mohammed; Devon, Karen; Kayssi, Ahmed; Goldfarb, Jeremy; Rossos, Peter; Cil, Tulin D.
Background. Text messaging has become ubiquitous and is being increasingly used within the health care system. The purpose of this study was to understand texting practices for clinical communication among staff surgeons at a large academic institution. Methods. Staff surgeons in 4 subspecialties (vascular, plastics, urology, and general surgery) were surveyed electronically. Results. A total of 62 surgeons from general surgery (n = 33), vascular surgery (n = 6), plastic surgery (n = 13), and urology (n = 10) completed the study (response rate 30%). When conveying urgent patient-related information, staff surgeons preferred directly calling other staff surgeons (61.5%) and trainees (58.8%). When discussing routine patient information, staff surgeons used email to reach other staff surgeons (54.9%) but preferred texting (62.7%) for trainees. The majority of participants used texting because it is fast (65.4%), convenient (69.2%) and allows transmitting information to multiple recipients simultaneously (63.5%). Most felt that texting enhances patient care (71.5%); however, only half believed that it enhanced trainees' educational experiences. The majority believed that texting identifiable patient information breaches patient confidentiality. Conclusions. Our data showed high adoption of text messaging for clinical communication among surgeons, particularly with trainees. The majority of surgeons acknowledge security concerns inherent in texting for patient care. Existing mobile communication platforms fail to meet the needs of academic surgeons. Further research should include guidelines related to texting in clinical practice, educational implications of texting, and technologies to better meet the needs of clinicians working in an academic surgical settings.